Sheikh Ahmad Al-Fatani and his Bisyaratul ‘Amilin wa Nazaratul ghafilin: a contribution in Hadith studies - Deraman, Fauzi; Wan Yusoff, Wan Mazwati; Suliaman, Ishak; Ahmad, Khadher; Abdullah, Mustaffa; Shah, Faisal Ahmad; Mohd Yusof, Mohd Yakub Zulkifli; Abd Razzak, Monika Munirah; Mohd Noor, Mohd Murshidi; Meftah, Jilani Touhami; Ariffin, Sedek; Kasar, Ahmad K.; et al. (IDOSI Publications, 2013)

(untitled)
Manuscripts on Hadith written by scholars from the Malay Archipelago had begun in the 17th century. Ahmad al-Fatani who is the subject of discussion in this present paper had written several manuscripts that can be categorized under the earliest writings in field of Hadith. Even though the obvious integral subjects of the writings were on similar discussions on tasawuf and fiqh, however he was evaluated and judged by his successors as a very meticulous and vigilant scholar with regards to transmitting Hadiths. He wrote both in Arabic and Malay languages. Among his manuscripts which were classified by Wan Mohd Saghir Abdullah as works on Hadith are Kitab Bisyaratul ‘Amilin Wa Nazaratul Ghafilin. This paper examines the main idea of his work which is considered as a reference in traditional madrasah system in the region.